Physical–chemical investigation of the oxidation reaction of biodiesel during storage in contact with carbon steel and 1020 steel in the presence of natural rosemary extract. Issue 1 (2nd January 2022) - Messias, Gabriel Benassi; Chendynski, Letícia Thaís; Gomes Mantovani, Ana Carolina; Suquila, Fábio Antonio Cajamarca; Tarley, César Ricardo Teixeira; Moreira, Ivanira; Borsato, Dionisio
Abstract: Biodiesel is a renewable fuel derived from oilseeds or animal fats. Biofuel has low oxidative stability due to the high content of esters of unsaturated fatty acids, which are easily oxidized when exposed to air, light, heat and metals. Antioxidants are added to biodiesel to retard the oxidative process, which can capture free radicals making them thermodynamically more stable. This study aims to analyze the oxidative stability of biodiesel in the presence of metallic alloys of carbon steel and 1020 steel with the presence of rosemary extract. The rosemary extract had a phenol content of of 25, 579 mgEAG /gdry mass, acting as antioxidant. In the presence of the natural rosemary extract, the biodiesel samples with metallic alloys but without rosemary extract presented similar oxidative stability and physicochemical properties, but when the rosemary extract is present, the carbon steel alloy presented a considerable compatibility, reaching higher induction periods. The thermodynamic parameters of the biodiesel sample with carbon steel and natural rosemary extract showed a significant improvement with the addition of antioxidant.